Effects of EU Enlargement to the Central European Countries on Agricultural Markets - Münch, Wolfgang (cege-Schriften, 2018)
Accession of the Central and Eastern European Countries is one of the biggest political projects for the European Union. As in all previous enlargements the agricultural chapter proves to be one of the most sensitive fields of the negotiations. This book examines the effects of enlargement on agricultural markets and government expenditure in the candidate countries as well as possible effects of different choices in the politically sensitive areas of direct payments and production quotas. The ten candidate countries have quite diverse economic and agricultural characteristics. Membership in the European Union, therefore, leads to varying macroeconomic effects. Two chapters specifically deal with these aspects and their effects on agriculture as well as likely country-specific developments in Hungary and in Slovenia. The quantitative tools developed and used for this analysis have also been more widely used by governments and institutions in analyses of questions related to enlargement. The book describes and documents these quantitative tools.